A Study on Financial Frauds In Organizations: - (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Data mining is able to uncover unknown patterns andpredict future trends and behaviors in financial markets. It createsopportunities for companies to make proactive and knowledge-driven decisions inorder to gain a competitive advantage. Data mining has been applied to a numberof financial applications, including development of trading models, investmentselection, loan assessment, portfolio optimization, fraud detection, bankruptcyprediction, real-estate assessment, and so on. The competitive advantagesachieved by data mining include increased revenue, reduced cost, and muchimproved marketplace responsiveness and awareness.